The Pragmatics of Professionalism: Translation and Interpretation in Puerto Rico and Quebec - Archibald, James (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1997)
AbstractThis article discusses the impact of official language policy on translation following the adoption of a 1993 law establishing Spanish/English bilingualism in Porto Rico. Using Quebec's official language legislation as an example, the author studies the possible long-lasting effects of language policy on the national and economic developemnt of Puerto Rico.